2014
DOI: 10.12740/app/32460
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Polish adaptation of the Adult Sibling Relationship Questionnaire (ASRQ)

Abstract: Summarybackground. Polish studies have not been focused on the method enabling a reliable and valid measure of the psychological attributes of sibling relationships in the period of adulthood. Aim. The aim of this study was to determine the psychometric properties of the Polish adaptation of the Adult Sibling Relationship Questionnaire (ASRQ). methods. The study included 406 students of different majors of the University of Łódź and the Łódź University of Technology. In the surveyed group, 58.9% were women (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Respondents were informed that participa-tion in the study was voluntary and anonymous and that the results would be used for research purposes only. Each person received a battery of tests consisting of a sociodemographic questionnaire, the STQ-Now (Polish version) and, depending on the subgroup they were assigned to: the ASRQ [22], the Loneliness Scale (UCLA) [23] or the Social Support Scale (SWS) [24].…”
Section: Methods Adaptation Proceduresmentioning
confidence: 99%
“…Respondents were informed that participa-tion in the study was voluntary and anonymous and that the results would be used for research purposes only. Each person received a battery of tests consisting of a sociodemographic questionnaire, the STQ-Now (Polish version) and, depending on the subgroup they were assigned to: the ASRQ [22], the Loneliness Scale (UCLA) [23] or the Social Support Scale (SWS) [24].…”
Section: Methods Adaptation Proceduresmentioning
confidence: 99%
“…It is not surprising that our sample was mainly made up of women, given that we collected our data via social media [69]. Moreover, female overrepresentation has been a recurring feature of research on adult sibships [16,70]. It is unlikely that having a more balanced sex ratio would have changed our results, as Bowman et al found no effect of sex on any of the three dimensions of sibling relationships (measured using the validated long version of the ASRQ) [1].…”
Section: Limitations and Future Research Directionsmentioning
confidence: 93%
“…It is not surprising that our sample was mainly made up of women, given that we collected our data via social media [69]. Moreover, female overrepresentation has been a recurring feature of research on adult sibships [16,70]. It is unlikely that having a more balanced sex ratio would have changed our results, as Bowman et al found no effect of sex on any of the three dimensions of sibling relationships (measured using the validated long version of the ASRQ) [1].…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%